2013
DOI: 10.7153/jmi-07-30
|View full text |Cite
|
Sign up to set email alerts
|

The weighted estimate for the commutator of the generalized fractional integral

Abstract: Abstract. Let L be the infinitesimal generator of an analytic semigroup on L 2 (R n ) with Gaussian kernel bound, and let L −α/2 be the fractional integral of L for 0 < α < n . Suppose that b is a locally integral function, then the commutator generated by b andMathematics subject classification (2010): 42B25, 42B20,42B35.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…When b belongs to the weighted Lipschitz spaces Lip β,ω , Hu and Gu [10] proved that [b, I α ] is bounded from L p (ω) to L q (ω 1−(1−α/n)q ) for 1/q = 1/p − (α + β)/n with 1 < p < n/(α + β). A similar result obtained when I α is replaced by the generalized fractional integral operator [7].…”
Section: Introduction and Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…When b belongs to the weighted Lipschitz spaces Lip β,ω , Hu and Gu [10] proved that [b, I α ] is bounded from L p (ω) to L q (ω 1−(1−α/n)q ) for 1/q = 1/p − (α + β)/n with 1 < p < n/(α + β). A similar result obtained when I α is replaced by the generalized fractional integral operator [7].…”
Section: Introduction and Resultssupporting
confidence: 73%
“…Chanillo [4] obtained a similar result when Calderón-Zygmund singular integral operators are replaced by the fractional integral operators. Recently, some Toeplitz type operators related to the singular integral operators are introduced, and the boundedness for the operators generated by singular integral operators and BMO functions or Lipschitz functions are obtained (see [5][6][7][8]).…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…Paluszyński (1995) showed that (homogeneous Lipschitz space) if and only if is bounded from to where and When b belongs to the weighted Lipschitz spaces Hu and Gu (2008) proved that is bounded from to for with A similar result obtained when is replaced by the generalized fractional integral operator (Hu et al. 2013). …”
Section: Introduction and Resultsmentioning
confidence: 99%